CORAK ESTETIKA PERTUNJUKAN WAYANG GAGRAG BANYUMAS SAJIAN CITHUT PURBOCARITO LAKON SRENGGINI TAKON RAMA - imam Sutikno; S Sunardi (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2018)
This research focuses on the populist aesthetic features of the Gagrag puppet show Banyumas Cithut Purbocarito presentation Srenggini Takon Rama, reveals the problem of: (1) Who is form of gagrag puppet show Banyumas Cithut Purbocarito presentation Srenggini Takon Ramadan (2) Who is the aesthetic style of leather puppet shows gagrag Banyumas Cithut Purbocarito Srenggini play Takon Rama. Both of these problems are examined using the aesthetic concept of puppetry, namely the concept of nuksma and mungguh. In addition, to reveal the structure of Banyumas gagrag puppet show using the Banyumas Gagrag Pedalangan Pathokan ... The results of this study indicate that the achievement of nuksma can be seen from the success of mastermind in building a seding atmosphere, team, trenyuh, greget, sereng, gandrung, and prenes. Indeed, it can be indicated through the harmony of taste in catur, sabet, and karawitan dance which is presented in each scene. Aesthetic analysis through the elements of pakeliran, including sabet, catur, and karawitan pakeliran, conclusions can be drawn about the aesthetics of Banyumas gagrag puppetry, namely nyopak.Keywords: aesthetics, Puppet Show, Cithut Purbocarito, Srenggini Takon Rama,